Early Surgical Treatment of High-grade Multiligamentous Knee Injuries. Issue 1 (March 2019) - Obremskey, William T.; Molina, Cesar; Richards, Justin E.; Staples, Kurtis S.; Streubel, Philipp N.; Avilucea, Frank
Abstract : Objectives: The aim of this study was to describe the clinical outcomes of patients with high-grade multiligamentous knee injuries treated with early surgery and range of motion. Design: This study was a case series. Setting: This study was conducted in the setting of an academic level-1 trauma center. Patients: Forty-seven patients (83% male individuals; average age 35 y; range, 18 to 70) with high-grade multiligamentous knee injuries were included in this study. Patients who had suffered knee dislocations III to V (KD III-KD V) (28 KD III, 16 KD IV, and 3 KD V injuries) between July 2006 and May 2014 were treated using a standard protocol of surgical treatment within 3 weeks of injury followed by early postoperative range of motion. Treatment: The treatment consisted of open primary repair [21/42 (50%), anterior cruciate ligament; 36/43 (83%), posterior cruciate ligament; 26/27 (92%), lateral cruciate ligament; 17/18 (96%), posterolateral corner] or allograft reconstruction with early range of motion. Main Outcome Measurements: The main outcome measurements were infection, range of motion, International Knee Documentation Committee, and Tegner and Lysholm scores at 12 months after surgery. Results: No patient had a postoperative deep wound infection requiring surgery. Two patients had a superficial infection that required oral antibiotics only. The average extension was 0 degrees. All but 1 patient achieved full extension; the patient developed a 5-degree flexion contracture. Mean active range of motion at 6 and 12 months was a mean arc of 119 and 123 degrees, respectively. Anterior tibiofemoral translation of >5 mm measured with KT-1000 was present in 6 (13%) patients. Six of the 47 patients (13%) had circumferential avulsions, and 1 patient with a poor subjective outcome had a concomitant complete patellar tendon avulsion in the setting of an open dislocation. One patient (2%) had laxity and instability requiring revision arthroscopic reconstruction of the posterior cruciate ligament and manipulation under anesthesia, and 3 patients required manipulation under anesthesia or open lysis because of stiffness. Fifteen (32%) patients reported knee function between 7 and 10 (competitive or higher) on the Tegner activity level scale. The mean International Knee Documentation Committee ±SD scores were 53.3±26.7 (range, 8 to 97.7) with 16/47 (34%) knees found to be normal, 13/47 (27.6%) near normal, 13 (27.6%) abnormal, and 5 (10.6%) severely abnormal. The mean Lysholm knee score was 75.4±22.1 (range, 25 to 98). No patient in the study had rotational instability at final follow-up with clinical assessment of posteromedial or posterolateral rotation (Dial test). Conclusions: Open operative treatment within the first 3 weeks of injury with primary repair or reconstruction of all injured structures can yield outcomes similar to those reported in patients treated with delayed or staged reconstruction of ligaments. Early treatment allows definitive management of injuries that are difficult to address on a delayed basis. Complications of infection, revision because of laxity, and stiffness are uncommon with this approach.